Workers’ Rights In Bankrupt Companies - Budi Santoso; Suwardi (Faculty of Law, Merdeka University Surabaya, Indonesia, 2026)
Corporate bankruptcy is a legal condition that directly affects the continuity of employment relationships between employers and workers/laborers. In practice, workers often find themselves in a weak position when a company is declared bankrupt, particularly regarding the fulfillment of normative rights such as wages, severance pay, and employment social security. Although statutory regulations grant workers a special status as preferred creditors, the implementation of these rights frequently encounters various legal and administrative obstacles. This situation creates legal uncertainty and potential injustice for workers/laborers. This study aims to analyze the legal protection of workers’ rights in companies declared bankrupt, as well as the legal standing of workers in bankruptcy proceedings under the applicable laws and regulations. The research method used is normative juridical research with statutory, conceptual, and case approaches. The findings show that although workers are positioned as preferred creditors, in practice workers’ rights are often not optimally fulfilled due to conflicts of interest with other creditors and the limited value of the bankruptcy estate. Therefore, stronger regulations and consistent law enforcement are needed to ensure fair protection of workers’ rights.